Anti-fertility efficacy of isolated compounds from leptadenia reticulata and lawsonia inermis - RAJESWARI J,; RANI S, (International Journal of Pharma and Bio Sciences, 2017)
Plant based traditional medicines for birth control has been in practice in rural populations of India, since time immemorial. Fast rise in population has caused serious issues within the economic process, resulting in impoverishment in developing countries like India. To control these issues Synthetic Abortifacient drugs were used which leads to major side effects. So the other urge towards medicinal plants have been used. Dry roots of Lawsonia inermis and whole plant of Leptadenia reticulata plant parts used traditionally by different ethnic communities in India for birth control. The present investigation is aimed to justify the scientific basis in traditional use of Lawsonia inermis and Leptadenia reticulata as anti-fertility agent. Compounds which is isolated from Leptadenia reticulata are 6-amino-3-hydroxy-4-(4'-methylphenyl)-2Hchromen-2-on is LR S1. The compounds isolated from the Lawsonia inermis was 3, 7, 4’, 5'-Tetrahydroxy-6 methoxyflavone is LI S1. Acute toxicity test of compounds was carried out in mice. The dose has been fixed as 200mg/kg. The abortifacient and anti-implantation activities of the compounds were investigated by Animal studies. The results revealed the effectiveness both in Anti-implantation and abortifacient activity. As a conclusion, the present study indicates that isolated flavonoid compounds shows the antifertility effect and it is safe at the effective antifertility doses used in this study.